Variability of Water Chemistry in Tundra Lakes, Petuniabukta Coast, Central Spitsbergen, Svalbard - Małgorzata Mazurek; Renata Paluszkiewicz; Grzegorz Rachlewicz; Zbigniew Zwoliński (The Scientific World Journal)
Samples of water from small tundra lakes located on raised marine terraces on the eastern coast of Petuniabukta (Ebbadalen, Central Spitsbergen) were examined to assess the changes in water chemistry that had occurred during the summer seasons of 2001–2003 and 2006. The unique environmental conditions of the study region include the predominance of sedimentary carbonate and sulphate rocks, low precipitation values, and an active permafrost layer with a maximum thickness of 1.2 m. The average specific electric conductivity (EC) values for the three summer seasons in the four lakes ranged from 242 to 398 μS cm−1. The highest EC values were observed when the air temperature decreased and an ice cover formed (cryochemical effects). The ion composition was dominated by calcium (50.7 to 86.6%), bicarbonates (39.5 to 86.4%), and sulphate anions. The high concentrations of HCO3−, SO42−, and Ca2+ ions were attributed to the composition of the bedrock, which mainly consists of gypsum and anhydrite. The average proportion of marine components in the total load found in the Ebbadalen tundra lake waters was estimated to be 8.1%. Precipitation supplies sulphates (as much as 69–81%) and chlorides (14–36%) of nonsea origin. The chief source of these compounds may be contamination from the town of Longyearbyen. Most ions originate in the crust, the active layer of permafrost, but some are atmospheric in origin and are either transported or generated in biochemical processes. The concentrations of most components tend to increase during the summer months, reaching a maximum during freezing and partially precipitating onto the bottom sediments.